Pengaruh Penggunaan Sosial Media terhadap Kecerdasan Emosional Dikalangan Remaja - Samiah Fitri Lestari; Irvia Eriza (Jurnal Syntax Transformation, 2021)
Influence is an attraction produced by objects or humans that can change a person's personality. The influence in this study is the power or strength generated by social media on emotional intelligence among teenagers at SMPN 28 Bekasi which is expected to be able to create teenagers who have character and character and are moral and bring change in a more advanced direction. Social media is an online medium, with its users being able to easily participate, share, and create content including blogs, social networks, wikis, forums and virtual worlds. Blogs, social networks and facebook. It is the most common form of social media used by people around the world. Social media is a forum that is able to create various forms of communication and provide various kinds of information for all circles of society. The social media referred to in this study is a microblog social networking site, which is an application that allows users to be able to connect by creating personal information so that they can connect with others. other people. Personal information can be such as photos, for example, facebook, instagram, path, twitter, whatsapp, etc.